2007
DOI: 10.1080/00207450600910259
|View full text |Cite
|
Sign up to set email alerts
|

Estrus Phase Differences in Female Rats in Morphine Antinociception Elicited From the Ventrolateral Periaqueductal Gray

Abstract: Male rodents display greater systemic morphine antinociception than females which show their most marked effects during late diestrus or proestrus. Morphine (1-2.5 mug) antinociception on the tail-flick test elicited from the ventrolateral periaqueductal gray was examined across estrus phases in female relative to male rats. Morphine antinociception was greatest in magnitude and potency in males followed by females tested during the proestrus phases relative to estrus and met-diestrus. These data confirm morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
1
6
1
1
Order By: Relevance
“…Experiment 2 of the present study suggests that the same is true when morphine is administered directly into the vPAG. Bodnar and colleagues report similar findings [47]. Thus, it is likely that sex differences were not observed in Experiment 1 because only 7% of females were in estrus during testing.…”
Section: Discussionsupporting
confidence: 66%
“…Experiment 2 of the present study suggests that the same is true when morphine is administered directly into the vPAG. Bodnar and colleagues report similar findings [47]. Thus, it is likely that sex differences were not observed in Experiment 1 because only 7% of females were in estrus during testing.…”
Section: Discussionsupporting
confidence: 66%
“…Previous research has found that antinociceptive sex-differences to morphine microinjection into the vlPAG are dependent on the estrus cycle [3, 34]. Although estrus phase was not measured, sex-differences in antinociception were evident in the present study.…”
Section: Discussioncontrasting
confidence: 51%
“…However, estrogen's actions may not be generalizable and may depend upon GPCR type, route of drug administration and therefore the site of action (spinal versus supraspinal), genotype and source of the experimental animals. Indeed, supraspinal morphine (a muopioid receptor agonist) injection produced most potent antinociception in the proestrous phase (high estrogen) relative to the met-diestrus phases (low estrogen) in SD rats from Charles River Laboratories (Kepler et al, 1989;Shane et. al., 2007), whereas Bernal et al (2007) reported the most potent morphine antinociception in the diestrous phase relative to the estrous phase in SD rats from Taconic Farms.…”
Section: Discussionmentioning
confidence: 99%